PANCASILA AS THE FOUNDATION OF THE STATE (COMPARATIVE STUDY OF THE VIEWS OF BUYA HAMKA AND MUNAWIR SJADZALI) - Muhammad Fadhillah; Sa'adatul Maghfira (Al Ushuliy: Jurnal Mahasiswa Syariah dan Hukum, 2024)
: The main problem in this research is Buya Hamka's view of Pancasila as the basis of the State and Munawir Sjadzali's view of Pancasila as the basis of the State. The aim of this research is to find out and explain Buya Hamka's views on Pancasila as the basis of the State and Munawir Sjadzali's views on Pancasila as the basis of the State. This type of research is normative research, with a library research type research method where the data obtained from primary legal materials are basic legal sources originating from the Al-Qur'an, Hadith, the 1945 Constitution of the Republic of Indonesia and the book Urat Tunggang Pancasila written by Buya Hamka, as well as primary legal materials obtained from books, journals, and articles related to Pancasila as the Foundation of the State (Comparative Study of the Views of Buya Hamka and Munawir Sjadzali).Judging from the results of this research, even though he had rejected Pancasila as the basis of the State, Buya Hamka had accepted Pancasila as the basis of the State finally and implemented Pancasila by emphasizing the Principle of Belief in One Almighty God in the sense of carrying out Allah's commands and abandoning His prohibitions. The values contained in Pancasila reflect values that have been prescribed by the Islamic religion. Munawir Sadjzali also accepted Pancasila as the final basis of the State. In fact, he emphasized that there was no obligation for Muslims to uphold Islam as the Foundation of the State, because in the Medina Charter, which became the constitution of the city of Medina when the Prophet Muhammad (SAW) led, he did not make Islam the basis of the State. Therefore, we, as Muslims, are obliged to accept and practice the existing principles of the State, which we know as Pancasila.